HUBUNGAN PENDIDIKAN SEKS DENGAN PERILAKU SEKSUAL PADA REMAJA PUTRI DI SMA NEGERI 4 BINJAI TAHUN 2017 - Wirda Faswita; Leny Suarni (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
Adolescent as a young generation is an important national asset because on its shoulder lies the responsibility of the nation's survival. Today's teenage problems are complex and worrying. this is due to the still low knowledge of adolescents about sex education. because of the curiosity of a large adolescent, in a condition where information and communication technologies are so free that teens get incorrect information. Then it will affect the value of their lives. Research method: The design of this study is an analytical survey with a cross-sectional approach to finding out the relationship between sex education with sexual behavior in adolescents in SMA Negeri 4 Binjai. Results and Discussion: Based on the results of Chi-Square test obtained respondents with good education Based on the research results obtained respondents with good education 88.3%, education less 11.7%, while the behavior is positive 48.7% and negative behavior 51.6%. Teenagers behaved well 41.4%, both behaved negative 46.9%, less education 7% positive behavior, less education 4.7% negative behavior. From the results of statistical tests with Chi-Square test found the relationship of sex education with sexual behavior obtained p-value = 0.340 has no effect on sexual behavior in adolescents. Conclusions: From the results of this study suggested to health workers at health centers khsusnya health promotion section to increase knowledge about sex education to adolescents to schools.Keyword:  sex education, sexual, behavior , adolescent